Analysis of the behaviour of Bacia of Côa agents (Interior North of Portugal) face to some European experiences pilot of Information Society - Ascens\~ao Maria Braga; José Carlos Zorrinho (European Regional Science Association (ERSA), 2005)
The deep development that has occurred in the last times to the level of the technologies of the information and communication was materialized in a true revolution of infrastructures, services and applications spread out by all the societies and seats on hiper sector of the information and that affect all the states, regions and citizens. The conscientious European Commission of this reality has become committed itself in the development of the Information Society in agreement clear on diverse elaborated documents and the launching of projects pilot. The development of the Information and Communication Technologies affects the everyday facilitating the fast access to the information that allows to face new challenges and to approximate the most isolated regions. But not all the regions are prepared to announce actively the Information Society. This work intends to know, based on the analysis of some of these projects pilot and its experiences, if the development agents of Bacia do Côa (North interior of Portugal) gather the essential conditions for the development of the Information Society.
Keywords: 330